Plataforma de tecno-desarrollo de materiales constructivos la Calera 2050: Plan parcial Satélite de tecno desarrollo ambiental (2017)
This text exposes an in depth analysis of tea municipality of the Calera, within the study emphasizes in social, environmental and economic dimensions. In this way it determines the existence of shortcomings within the planning instruments established for the municipality; Because it is reflected a scheme of a bedroom city where its inhabitants are in need of migration to the megalopolis of Bogota in order to search for opportunities in social and educational work. The main affected is the municipality since its urban structuring, road connection and its planning over time has not been appropriate, thus generating a decline in socioeconomic and environmental aspects. The total ignorance of the municipality as an environmental power is generated thanks to the little planning and development and infrastructure of public works in the region or province of Guavio; The search for lime as a competitive municipality in a globalized world is projected through urban management tools, structuring models of satellite city and garden. A partial techno-environmental plan is proposed for the protection and development of environmental biodiversity, obtaining knowledge of the government plans and the POT in order to obtain the epicenter of technology and development of environmental building materials Guavio.